Vertical Production Networks in Multinational Firms - Hanson, Gordon H.; Mataloni, Raymond J.; Slaughter, Matthew J. (The Review of Economics and Statistics, 2005)
In recent decades, growth of world trade has been driven largely by rapid growth of trade in intermediate inputs. Much of input trade involves multinational firms locating input processing in their foreign affiliates, thereby creating global vertical production networks. We use firm-level data on U.S. multinationals to examine trade in intermediate inputs for further processing between parent firms and their foreign affiliates. Among our main findings are that demand for imported inputs is higher when affiliates face lower trade costs, lower wages for less-skilled labor, and lower corporate income tax rates.